Detection of All Single-Base Mismatches in Solution by Chemiluminescence - Nelson, Norman C.; Hammond, Philip W.; Matsuda, Eiji; Goud, Anil A.; Becker, Michael M. (Nucleic acids research, 1996)
A rapid in-solution method for the detection of all 12 single-base mismatches is described. The technique is based on the hybridization protection assay (HPA) format that utilizes oligonucleotide probes labeled with a highly chemiluminescent acridinium ester (AE). Hydrolysis by weak base renders AE permanently non-chemiluminescent. When an AE-labeled probe hybridizes to an exactly complementary target, AE is protected from hydrolysis relative to the unhybridized conformation. Single-base mutations in the duplex adjacent to the site of AE attachment disrupt this protection resulting in rapid AE hydrolysis and loss of chemiluminescence. The discrimination effect was seen in both DNA and RNA. Studies of Tm values revealed that this effect is not due to a decrease in the overall stability of the duplex, suggesting the AE is responding to local structural changes in the double helix induced by mismatches. Using this principle all 12 single mismatches were clearly discriminated from the corresponding matched sequences. The assay is homogeneous, simple, sensitive, applicable to both amplified and non-amplified targets, and is completed in 30–60 min. An example showing discrimination between wild-type and mutant sequences corresponding to the reverse transcriptase coding region of HIV-1 is given.